Mobilizing Europe's citizens to take action on migration and climate change: behavioral evidence from 27 EU member states - Heiko Giebler; Johannes Giesecke; Macartan Humphreys; Swen Hutter; Heike Klüver (Journal of European Public Policy, 2025)
This paper investigates how two politicized issues – migration and climate change – mobilize citizens across European countries. Building on the concept of issue-specific mobilization potentials, we examine citizens' willingness to support petitions related to the two issues using an original behavioral measure embedded in the 2024 European Parliament Election Study. We document variation in political engagement and examine how opposing stances on issues owned by the left or the right mobilize citizens, how citizens' agreement with issue positions affects support, and whether grievances, participation cultures, politicization levels, and the ideology of the national government can explain national-level variation. Our results indicate substantial variation in petition support across countries and issues, with the right-wing petition on migration attracting the most support. However, our country-level measures do not explain this variation well. Overall, our findings highlight the need for more nuanced, issue-specific approaches to understanding cross-national patterns of political participation.
Keywords: 320; nonelectoral political participation; issue-specific mobilization potential; migration; climate change; European Union